2015
DOI: 10.1080/02786826.2014.998363
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characterization and Oxidative Reactivity Evaluation of Aged Brake Wear Particles

Abstract: Brake wear dust is a significant component of traffic emissions and has been linked to adverse health effects. Previous research found a strong oxidative stress response in cells exposed to freshly generated brake wear dust. We characterized aged dust collected from passenger vehicles, using microscopy and elemental analyses. Reactive oxygen species (ROS) generation was measured with acellular and cellular assays using 2 0 7-dichlorodihydrofluorescein dye. Microscopy analyses revealed samples to be heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Several toxicological studies have shown that particles in the nanometer scale are particularly dangerous as they can enter the blood stream through the lungs (Oberdörster 2005, Oostingh 2013. Furthermore, metallic brake wear particles damage tight junctions within the mechanisms that involve oxidative stress (Gasser et al, 2009;Zhao et al, 2015); therefore, the important point is not only the particle mass, but also the particle quality (e.g. chemical composition and biological effect).…”
Section: Discussionmentioning
confidence: 99%
“…Several toxicological studies have shown that particles in the nanometer scale are particularly dangerous as they can enter the blood stream through the lungs (Oberdörster 2005, Oostingh 2013. Furthermore, metallic brake wear particles damage tight junctions within the mechanisms that involve oxidative stress (Gasser et al, 2009;Zhao et al, 2015); therefore, the important point is not only the particle mass, but also the particle quality (e.g. chemical composition and biological effect).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the ROS production potential of welding fume particles using the DCFH assay, which has been widely applied for non-specific ROS detection ( Venkatachari et al , 2007 ; Jiang et al , 2008 ; Aranda et al , 2013 ; Zhao et al , 2014 ) and found to be relatively inexpensive and robust. Regarding the reported limitations of this assay in the literature ( Hoet et al , 2013 ; Pal et al , 2014 ), we carefully applied the strategies published in the study by Zhao and Riediker (2014) to achieve better performance of the assay and avoid artefacts, such as to always keep an appropriate control to exclude ROS produced by self-oxidation of the reagents and analyse the standards with samples at the same time point.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding TEM, it is one of the most complete characterization tools for nanostructured systems [145,146]. Sample preparation can be tricky, and one of the methods is preparing a suspension of wear particles in ethanol (with a preceding set of steps), from which a single drop is deposited onto the TEM gold [90] or Cu [147] grid. Gold is preferable since provides X-ray emission lines which can be easily separated from the genuine ones, coming from the specimen.…”
Section: Characterizing Wear Debrismentioning
confidence: 99%